(untitled) (gjstudies, 2017)
This research investigates the relationship between accounting practices and thefinancial sustainability of small and medium enterprises (SMEs), proposing a novel,integrated framework that moves beyond traditional compliance-based accountingmodels. While prior literature often treats accounting as a mere regulatory necessity or a tool for historical reporting, this study conceptualizes it as a dynamic,strategic capability for proactive financial resilience. We introduce the concept of’Adaptive Resource Accounting’ (ARA), a methodology that synthesizes principles from ecological resource management, lean systems thinking, and behavioralfinance into a cohesive accounting practice tailored for SME volatility. The centralresearch question examines how SMEs can reconfigure their accounting practicesfrom backward-looking record-keeping to forward-looking sustainability navigationsystems. Our methodology employs a longitudinal, mixed-methods design, combining in-depth case studies of 45 SMEs across three sectors with agent-based modeling to simulate the impact of different accounting practice regimes on long-termfinancial viability under stochastic market conditions. The results demonstratethat SMEs implementing ARA principles, such as non-linear cash flow forecasting, resilience buffer quantification, and stakeholder value flow mapping, exhibit astatistically significant 34% higher probability of maintaining positive operationalcash flow during economic downturns compared to peers using standard practices.Furthermore, the study reveals a previously under-explored linkage: the granularity and frequency of managerial accounting information, when focused on leadingindicators of resource consumption rather than purely financial outcomes, directlycorrelate with more agile strategic pivots. The findings challenge the prevailing sumption that sophisticated accounting is cost-prohibitive for SMEs, instead showing that strategically simplified, yet conceptually richer, practices are a critical leverfor sustainability. This contribution is original in its cross-disciplinary theoreticalfoundation and its empirical demonstration of how accounting practice design, notjust adoption, fundamentally shapes the financial trajectory of smaller enterprises